2004
DOI: 10.1128/iai.72.2.949-957.2004
|View full text |Cite
|
Sign up to set email alerts
|

CpG Oligodeoxynucleotide and Montanide ISA 51 Adjuvant Combination Enhanced the Protective Efficacy of a Subunit Malaria Vaccine

Abstract: Unmethylated CpG dinucleotide motifs present in bacterial genomes or synthetic oligodeoxynucleotides (ODNs) serve as strong immunostimulatory agents in mice, monkeys and humans. We determined the adjuvant effect of murine CpG ODN 1826 on the immunogenicity and protective efficacy of the Saccharomyces cerevisiae-expressed 19-kDa C-terminal region of merozoite surface protein 1 (yMSP1 19 ) of the murine malaria parasite Plasmodium yoelii. We found that in C57BL/6 mice, following sporozoite challenge, the degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
62
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 42 publications
3
62
0
1
Order By: Relevance
“…This might be consistent with Saavedra's report that showed the CpG-driven Th1 response was not enough for protection against the virulent T. gondii strain (33). Like others (22,24,32), our results confirm that CpG ODNs are excellent Th1 adjuvants and that the inversion from CpG to GpC eliminates this ability to induce an immune response in vivo.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This might be consistent with Saavedra's report that showed the CpG-driven Th1 response was not enough for protection against the virulent T. gondii strain (33). Like others (22,24,32), our results confirm that CpG ODNs are excellent Th1 adjuvants and that the inversion from CpG to GpC eliminates this ability to induce an immune response in vivo.…”
Section: Discussionsupporting
confidence: 82%
“…Synthetic ODN containing unmethylated CpG motifs act as an immune adjuvant in mammals, boosting the humoral and cellular response to co-administered (21,37). CpG ODN has been used as an adjuvant for the clearance of many intracellular pathogens (8,11,14,20,24,25). Moreover, CpG is currently being used in human trials with promising results (1,7), an advantage over the commonly used experimental adjuvant not authorized for human use.…”
mentioning
confidence: 99%
“…It is widely reported that oily emulsions create an inflammation at inoculation sites, promoting the recruitment of APCs like macrophages and lymphocytes. 18,20 This finding suggests that emulsive formulation could enhance the antibodies induction during first stages of immune response due to the presence of the oily component. Although experiments should be addressed to evaluate if 100 μg non-emulsive formulation even up with 100 μg emulsive formulation in later days after fourth immunization we speculate they level off but slower than 200 μg formulations did.…”
Section: Discussionmentioning
confidence: 75%
“…18,45 In contrast to adenoviral vaccine, co-injection of CpG ODN with plasmid vectors has been associated with increase CTL response. [46][47][48] A few reports in prime-boost protocols described the use of recombinant vaccinia virus following antigenic peptide and CpG ODN to promote the CTL responses. 49,50 It will be interesting to understand if the dichotomy (suppressed CD81 T cell responses of enhanced anti-tumor immunity) is unique to adenovirus in combination with CpG ODN since adenovirus is a DNA virus and may activate TLR9 on its own or other TLR ligands that interact with TLR9 pathway.…”
Section: Discussionmentioning
confidence: 99%